Protein Tyrosine Phosphatases and Type 1 Diabetes: Genetic and Functional Implications of PTPN2 and PTPN22 (The Review of Diabetic Studies, 2023)
Protein tyrosine phosphatases (PTPs) play a central role in modulating the transduction of cellular signals, including the cells of the immune system. Several PTPs, PTPN22, PTPN2, and UBASH3A, have been associated with risk of type 1 diabetes (T1D) by genome wide association studies. Based on the current understanding of PTPs, it is clear that these variants impact antigen receptor signaling and cytokine signaling. This impact likely contributes to the development and progression of autoimmunity through multiple mechanisms, including failures of central and peripheral tolerance and the promotion of proinflammatory T cell responses. In this review, we discuss the genetic and functional implications of two of these PTPs, PTPN22 and PTPN2, in the development of T1D. We describe the known roles of these proteins in immune function, and how the expression and function of these proteins is altered by the genetic variants associated with T1D. Yet, there are still controversies in the field that require further study and the development of new approaches to extend our understanding of these PTP variants, with the goal of using the information gained to improve our ability to predict and cure T1D.